Late Manipulation under Anesthesia after Total Knee Arthroplasty: Improved Range of Motion and a Low Complication Rate - Weintraub, Matthew T.; Kurina, Steven J.; Cline, Joseph T.; Forlenza, Enrico M.; Berger, Richard A.; Gerlinger, Tad L. (The Journal of Knee Surgery, 2024)
The purpose of this study was to evaluate outcomes of late manipulation under anesthesia (MUA) for stiffness performed from ≥12 weeks to more than a year after primary total knee arthroplasty (TKA). A total of 152 patients receiving MUA ≥12 weeks after primary TKA from 2014 to 2021 were reviewed. The primary outcome measured was change in range of motion (ROM). We tracked intraoperative complications and the need for repeat MUA or open procedure for continued stiffness after initial MUA. Three subgroups were analyzed: Group 1 included 58 knees between 12 weeks and 6 months after TKA, Group 2 included 44 knees between 6 and 12 months after TKA, and Group 3 included 50 knees ≥12 months after TKA. Analysis included descriptive statistics and univariate analysis, with α <0.05. Groups 1 to 3 all significantly increased their overall ROM by 20.9, 19.2, and 22.0 degrees, respectively. All groups significantly increased their flexion and extension from preoperatively. Group 1 had one intraoperative supracondylar femur fracture (1.7%) requiring open reduction and internal fixation, and five patients required repeat MUA or open procedure (8.6%). Group 2 had no intraoperative fractures, and five patients required repeat MUA or open procedure (11.4%). Group 3 had one intraoperative tibial tubercle avulsion fracture managed conservatively (2.0%) and one repeat MUA (2.0%). Late MUA resulted in significantly improved ROM in all groups. ROM improved more as the time from index TKA increased, although statistically insignificant. Repeat MUA or open procedure rate decreased with MUA ≥12 months from TKA, although statistically insignificant. The overall intraoperative fracture risk was 1.3%.
Keywords: manipulation under anesthesia; total knee arthroplasty; stiffness; range of motion